The electrophysiological effects of Tongyang Huoxue granules on the ignition phase during hypoxia/reoxygenation injury in sinoatrial node cells - Wu, Qiaomin; Chang, Xing; Wang, Yanli; Liu, Jinfeng; Guan, Xuanke; Liu, Zhiming; Liu, Ruxiu (Frontiers in Physiology, 2024)
Introduction: This study was undertaken to explore the potential therapeutic effects of Tongyang Huoxue Granules (TYHX) on sinoatrial node (SAN) dysfunction, a cardiac disorder characterized by impaired impulse generation or conduction. The research question addressed whether TYHX could positively influence SAN ion channel function, specifically targeting the sodium-calcium exchanger (INCX) and L-type calcium channel (ICaL) of the SAN. Methods: Sinoatrial node cells (SANCs) were isolated and cultured from neonatal Japanese big-eared white rabbits within 24 hours of birth. The study encompassed five groups: Control, H/R (hypoxia/reoxygenation), H/R+100 μg/mL TYHX, H/R+200 μg/mL TYHX, and H/R+400 μg/mL TYHX. The H/R model, simulating hypoxia/reoxygenation stress, was induced within 5 days of culture. Whole-cell patch clamp technique was employed to record currents following a 3-minute perfusion and stabilization period with TYHX. Results: TYHX administration demonstrated improvements in the ignition phase of impaired SANCs. The half-maximal effective dose of TYHX, as determined by SANC beating frequency, was found to be 323.63 μg/mL. Inward current density of INCX increased in response to TYHX (200 and 400 μg/mL), while TYHX enhanced ICaL current density in H/R SANCs, with 400 μg/mL exhibiting greater efficacy. Additionally, TYHX regulated the gating mechanisms of ICaL by right-shifting the steady-state inactivation curve and accelerating recovery from inactivation. Notably, TYHX increased the activation time constant under 200 and 400 μg/mL, prolonged the fast inactivation time constant τ1 with 400 μg/mL, and extended the slow inactivation time constant τ2 with 100 and 400 μg/mL. Discussion and Conclusion: The findings suggest that TYHX may hold promise as a therapeutic intervention for sinus node dysfunction, offering potential avenues for drug development aimed at safeguarding SAN function.